2014
DOI: 10.1371/journal.pone.0098748
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Association between Lumican Gene Polymorphisms and Susceptibility to High Myopia

Abstract: BackgroundsMany studies have evaluated the association between lumican (LUM) gene polymorphisms and high myopia. However, the results remain controversial. This meta-analysis aims to comprehensively evaluate the relationship between two common LUM polymorphisms (rs3759223 and rs3759222) and the risk of high myopia.MethodsA comprehensive literature search for studies published up until September of 2013 was performed. Data were extracted independently by two investigators, and the weighted Odds Ratios (ORs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
0
3
1
Order By: Relevance
“…On the other hand, in our Japanese population, the genotype tests showed that the T allele had a stronger association with high myopia in a dominant model than in a recessive model, regardless of the SE level of the patients (Table 3). This finding is not in line with previous studies 2628…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in our Japanese population, the genotype tests showed that the T allele had a stronger association with high myopia in a dominant model than in a recessive model, regardless of the SE level of the patients (Table 3). This finding is not in line with previous studies 2628…”
Section: Discussioncontrasting
confidence: 98%
“…Recent meta-analyses of the genotype results for rs3759223 that were reported in previous studies suggest that rs3759223 is associated with an increased risk of high myopia in a recessive model of the T allele 2628Table 4 shows the results of genotypic association tests that used the genotype results reported by each study; the T allele was associated with an increased risk of high myopia in a recessive model in all of the studies.…”
Section: Discussionmentioning
confidence: 97%
“…The SLRPs are a subfamily of the large (>300 members) leucine-rich repeat (LRR) superfamily [58] a Lum tm1Wwk [60] Cancer [12,86] Systemic lupus erythematosus [88] Myopia [90] Fibromodulin Class II SLRP [61] Congenital stromal corneal dystrophy [153,154,156] Marfan syndrome [155] Progeroid symptoms [107] Cancer [12] Biglycan that includes the toll-like receptors (TLRs) and NOD-like receptors [14]. The LRR superfamily is characterized by tandem repeats of leucine-rich motifs of 21, 24 or 26 amino acids, classified into seven different types based on conserved amino acids.…”
Section: Slrp Classification and Evolutionary Relationshipsmentioning
confidence: 99%
“…Lumican expression is induced in fibroblast cultures by proinflammatory signals such as lipopolysaccharides or IL‐1β and suppressed by immunosuppressive TGFβ . Polymorphisms in LUM , and changes in its expression levels have been associated with multiple diseases, ranging from cancer to systemic lupus erythematosus and myopia . Table shows the key cellular functions associated with each of the five SLRPs, as well as the available gene‐targeted mouse models and key associations with some human disease (this is not a complete list of all disease associations).…”
Section: Slrps and Their Interactions With Ligands Growth Factors Amentioning
confidence: 99%